Exploring the Role of Universities in the Sustainability of Malaysian Bumiputera Technology-Based Firms - Umar Haiyat, Abdul Kohar; Hamrila, Abdul Latip; Aniza, Othman (Malaysian Institute Of Management, 2014)
Previous studies suggest that academics and researchers working in universities and other institutions of higher education play an important role in ensuring the sustainability of technology entrepreneurship. The intent of this exploratory qualitative study is to extend our understanding of the roles of universities in assisting Malaysian Bumiputera technology-based firms (TBFs) to sustain their business. Based on an inductive qualitative approach, this study has uncovered three main roles of university academics in the sustainability of Bumiputera TBFs: 1) cultivating entrepreneurial cultures, 2) commercialising university research, and 3) strengthening university-industry linkages.